2012
DOI: 10.1159/000335919
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Endophenotypes and Polymorphisms in the Histamine Receptor <b><i>HRH4</i></b> Gene

Abstract: Background: Histamine as an inflammatory mediator plays an important role in chronic allergic and asthmatic conditions. However, the role of genetic polymorphisms of the histamine receptor HRH4 (histamine receptor H4) gene in asthma susceptibility and endophenotypes has not been studied yet. Our aim was to investigate the possible association between single nucleotide polymorphisms (SNPs) in the HRH4 gene and asthma or some endophenotypes of asthma. Methods: Twenty-one SNPs of the HRH4 gene were genotyped in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Along this line, keratinocytes derived from patients with atopic dermatitis expressed higher levels of the H 4 receptor mRNA compared with keratinocytes from patients without skin disease or psoriasis (Glatzer et al, 2013). In asthma, there appeared to be a link between three single nucleotide polymorphisms in the H 4 receptor gene and infectioninduced asthma (Simon et al, 2012). mRNA encoding the H 4 receptor was significantly higher expressed and H 4 receptor gene copy numbers were significantly amplified in patients with systemic lupus erythematosus compared with healthy controls.…”
Section: Anatomic Frameworkmentioning
confidence: 94%
“…Along this line, keratinocytes derived from patients with atopic dermatitis expressed higher levels of the H 4 receptor mRNA compared with keratinocytes from patients without skin disease or psoriasis (Glatzer et al, 2013). In asthma, there appeared to be a link between three single nucleotide polymorphisms in the H 4 receptor gene and infectioninduced asthma (Simon et al, 2012). mRNA encoding the H 4 receptor was significantly higher expressed and H 4 receptor gene copy numbers were significantly amplified in patients with systemic lupus erythematosus compared with healthy controls.…”
Section: Anatomic Frameworkmentioning
confidence: 94%
“…To date, little is known about the genetics of CS-induced neutrophilic airway inflammation, in contrast to the genetics of COPD or asthma for which many susceptibility genes have been identified (8,38). Although some studies have already investigated the genetics of emphysema in COPD as well as different endophenotypes of asthma (13,47), to our knowledge no studies investigating the genetics of CS-induced neutrophilic airway inflammation have been performed.…”
mentioning
confidence: 99%
“…allergic asthma, exercise induced asthma). In their study, where allergic asthma was defined by environmental allergy skin prick testing, they also did not find an association between the HRH4 413C/T SNP and the disease [42]. However, they did identify an association between other variants, which were not included in our study (HRH4 rs527790, rs487202, rs17187619) and "infection-induced asthma".…”
Section: Discussionmentioning
confidence: 66%
“…Although the functional significance of many of these SNPs is unknown, several studies have been conducted to explore potential associations between histamine related genes and asthma and allergic disease [6,17,[33][34][35][36][37][38][39][40][41][42][43]. We have previously reported that the HRH1 gene was more highly expressed in buccal tissue from those with asthma compared to those without asthma [44].…”
Section: Introductionmentioning
confidence: 99%